Mid-facial skeletal and soft tissue changes after maxillary skeletal expander application: a retrospective CBCT study - Arzu Alan; Yeşim Kaya; Kevser Sancak (BMC Oral Health)
Abstract Background The increased resistance of midpalatal, zygomaticomaxillary, and pterygopalatine sutures over time reduces the dentofacial orthopedic effect of conventional expanders. To address this, mini-screw-assisted rapid palatal expanders have been developed. The aim of this study was to investigate the mid-facial soft tissue changes along with rotational movements of zygomaticomaxillary complex after maxillary skeletal expander 2 (MSE 2) application. Methods Pre- and post-expansion CBCT images of 17 patients (10 female, 7 male) with transversal maxillary deficiency and treated with MSE 2, were enrolled in this retrospective study. Eight skeletal angular measurements were performed in the coronal and axial zygomatic sections. Besides, nineteen linear and three angular soft tissue measurements were investigated in the midsagittal plane. All the measurements were performed using OnDemand3D software. Paired t-test was used to compare the pre- and post-expansion outcomes. Results In the coronal zygomatic section, the decrease in frontoethmoidal angle (-2.39°, p = 0.006) and increases in frontozygomatic (R:3.04° (p = 0.001); L:3.01° (p = 0.001)) and zygomaticomaxillary (R:1.36° (p = 0.001); L:1.22° (p = 0.05)) angles revealed the outward rotation of the zygomaticomaxillary complex. The increase in maxillary inclination (R:2.75° (p = 0.001); L:2.76° (p = 0.003)) showed the downward rotation of zygomaticomaxillary complex. The increases in frontozygomatic, frontoalveolar (R:2.77° (p = 0.001); L:2.64° (p = 0.001)) and frontodental (R:2.49° (p = 0.001); L:2.07° (p = 0.001)) angles represented greater skeletal expansion and minimal alveolar bone bending and dental tipping. Soft tissue measurements revealed significant increase in upper (1.47 mm (p = 0.002)) and lower (1.56 mm (p = 0.009)) face heights, alar nasal width (R: 0.67 mm (p = 0.001); L: 0.95 mm (p = 0.002)), nasal tip protrusion (0.83 mm (p = 0.03)), vertical philtrum height (0.25 mm (p = 0.037)), and nasal width angle (4.60° (p = 0.001)), and a decrease in the facial profile angle (2.49° (p = 0.037)). Conclusion Downward and outward rotation of the zygomaticomaxillary complex around the fulcrum area above the superior aspect of the frontozygomatic suture resulted in significant soft tissue changes in the paranasal and nasal regions.